2013
DOI: 10.1128/jvi.02848-12
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Targets Arbovirus Replication in Culicoides Cells

Abstract: cArboviruses are transmitted to vertebrate hosts by biting arthropod vectors such as mosquitoes, ticks, and midges. These viruses replicate in both arthropods and vertebrates and are thus exposed to different antiviral responses in these organisms. RNA interference (RNAi) is a sequence-specific RNA degradation mechanism that has been shown to play a major role in the antiviral response against arboviruses in mosquitoes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
110
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 79 publications
8
110
0
1
Order By: Relevance
“…Dicer-2 may act upon the genome of the virus itself-as in the case of dsRNA viruses-and/or on viral replication and transcription intermediates, although structured, single-stranded RNA (ssRNA) may also be utilized (4). Interestingly, several deepsequencing data have revealed that approximately 18-to 30-nt viral small RNAs (vsRNAs) of infected insects are not evenly distributed along the genomes but map preferentially in distinct genomic areas (hot spots) versus genomic stretches with unmapped or less-mapped vsRNAs (cold spots) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The origin of these profiles, as well as the hypothetical functional distinction between vsRNAs deriving from hot or cold spots, remains substantially elusive, although hot spots near the end of the genome have been attributed to structured regulatory viral regions (14) and an RNAi decoy-like mechanism driven by abundant vsRNAs has been proposed by another group (15).…”
mentioning
confidence: 99%
“…Dicer-2 may act upon the genome of the virus itself-as in the case of dsRNA viruses-and/or on viral replication and transcription intermediates, although structured, single-stranded RNA (ssRNA) may also be utilized (4). Interestingly, several deepsequencing data have revealed that approximately 18-to 30-nt viral small RNAs (vsRNAs) of infected insects are not evenly distributed along the genomes but map preferentially in distinct genomic areas (hot spots) versus genomic stretches with unmapped or less-mapped vsRNAs (cold spots) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). The origin of these profiles, as well as the hypothetical functional distinction between vsRNAs deriving from hot or cold spots, remains substantially elusive, although hot spots near the end of the genome have been attributed to structured regulatory viral regions (14) and an RNAi decoy-like mechanism driven by abundant vsRNAs has been proposed by another group (15).…”
mentioning
confidence: 99%
“…The different replication strategies of these viruses may require different control mechanisms. The recent discovery of putative new antiviral responses such as melanisation and, particularly, the implication of piRNAs in mosquito antiviral immunity against a variety of arboviruses (CHIKV, SFV, SINV, DENV, LACV, RVFV, SBV and BTV) [45,68,82,102,103,123], show how complex the arthropod immune system is and how far there is still to go in understanding it. One of the questions that will surely be addressed in the future is how virus-derived piRNAs are generated and whether it is possible to use the knowledge gained to benefit vector control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In cells derived from Culicoides biting midges, viRNAs with PIWI signature have been observed after infection with bluetongue virus (BTV) and Schmallenberg virus (SBV) [103], suggesting this newly-discovered antiviral mechanism is not only a mosquito-specific response. Future work on other vector species including ticks will elucidate whether this mechanism has evolved in specific groups of dipteran vector species or is also an antiviral response in other arthropods.…”
Section: Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode of replication raises an interesting question: do dsRNA viruses escape from dsRNA-mediated antiviral responses, including RNA silencing? Some studies have detected vsRNAs, which are a hallmark of RNA silencing, from dsRNA viruses in insects using next-generation sequencing (NGS), including reoviruses (20)(21)(22), a totivirus (23), and entomobirnaviruses (24,25). These data suggested that encapsidated dsRNA viruses are also a target of RNA silencing.…”
mentioning
confidence: 95%